Kajian Perubahan Kondisi Ekologi Wilayah DAS Garang dan Aktivitas Penduduk yang Mempengaruhinya - Munthe, Megawati Budiarta; Handayani, Wiwandari (Jurusan Perencanaan Wilayah dan Kota, 2024)
Garang watershed is one of the watersheds of Central Java. Garang watershed acts as a supplier of clean water for PDAM Tirta Model. Garang watershed is also one of the strategic areas in terms of function and environmental carrying capacity. The position as part of the determination of regional ecology also makes it important to maintain the ecology of the watershed. The ecological condition of the watershed area is influenced by its components, namely climate, flora and fauna, water, soil or land, and humans. The purpose of the study was to examine changes in the ecological conditions of the Garang watershed in 2010 and 2020 as well as changes in population activities in their utilization. The research was conducted using quantitative research methods. The analytical techniques used are spatial analysis and descriptive statistical analysis. The data used in the form of secondary data includes satellite imagery of the Garang watershed in 2010 and 2020 as well as data on the population and livelihoods of the Garang watershed residents in 2010 and 2017. The results showed a large change in the ecological conditions of the Garang watershed, where the vegetation density decreased by 60%, the wetness of the land increased, the dryness of the land improved, and the land cover shifted 40% to built up, open land, and industry.